Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas VIII pada Materi Sistem Pernapasan Manusia - Shintani Rambu Djati; Yohana Makaborang; Yohana Ndjoeroemana (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to improve the learning outcomes of class VIII students of SMP Negeri 2 Waingapu through the application of the Problem Based Learning learning model. This type of research is Classroom Action Research (PTK) which is conducted in two cycles, which consists of four stages, namely: planning, implementation, observation stage, and reflection stage. Before going to cycle I and cycle II, the researcher first conducted a pre-cycle. The subjects of this study were 31 students in class VIII of SMP Negeri 2 Waingapu for the academic year 2022/2023, consisting of 17 male students and 14 female students. The data obtained in this study are in the form of student learning outcomes taken from the application of the Problem Based Learning learning model. The instruments used are interviews, tests, and documentation. The results of the research and data analysis in cycle I and cycle II revealed that there was an increase in the learning outcomes of class VIII students of SMP Negeri 2 Waingapu for the 2022/2023 academic year. This is indicated by an increase in the proportion of student learning outcomes in Biology lessons on the material of the human respiratory system. The results showed that the proportion of student learning outcomes in pre-cycle was 29%, cycle I was 75%, and cycle II was 90%. The conclusion of this study is that the application of the Problem Based Learning learning model can improve the learning outcomes of class VIII students of SMP Negeri 2 Waingapu.